Investigation of Times of Minima of Selected Early-Type Eclipsing Binaries - Mayer, Pavel; Wolf, Marek; Niarchos, P. G.; Gazeas, K. D.; Manimanis, V. N.; Chochol, Drahomír (Astrophysics and Space Science, 2006)
New precise times of minimum light for several early-type eclipsing binaries were obtained at three observatories. The changes of period of the following measured binaries are discussed: V1182 Aql, LY Aur, SZ Cam, FZ CMa, QZ Car, LZ Cen, V606 Cen, AH Cep and TU~Mus.
Keywords: Eclipsing binary; Light-time effect; Period changes